A date with Destiny. - Watson, Tom (New Statesman, 2014)
The article reviews video games including "Call of Duty: Advanced Warfare--Day Zero Edition," "Grand Theft Auto V" from Rockstar Games, and "Wolfenstein: The New Order" from Bethesda Softworks.